2011
DOI: 10.1039/c0gc00647e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cradle-to-gate life cycle assessments of cellulose dissolution with 1-butyl-3-methylimidazolium chloride and N-methyl-morpholine-N-oxide

Abstract: In this paper the expected environmental impacts of the industrial cellulose dissolution with the ionic liquid 1-butyl-3-methylimidazolium chloride (Bmim Cl) were analyzed through a "cradle to gate" Life Cycle Assessment (LCA). In order to weigh up the "greenness" of the process, the analysis was performed through a comparison with the well established environmental friendly N-methyl-morpholine-N-oxide (NMMO)/H 2 O process. Although dissolution of cellulose in Bmim Cl has not been used for industrial productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 31 publications
0
73
0
Order By: Relevance
“…Previous LCA case studies demonstrated that green solvents have an environmental footprint and that in some cases trade-offs exist between several environmental impact categories for different feedstock (Dom enech et al, 2002;Marquevich et al, 2002;Miller et al, 2007;Righi et al, 2001). In addition, existing studies on LCA (Do Amaral, 2004;Kukfisz and Maranda, 2014;Ophus and Digernes, 1996) of emulsion chemistry point out the need to assess the environmental cost/benefits of emulsion technologies.…”
Section: Introductionmentioning
confidence: 92%
“…Previous LCA case studies demonstrated that green solvents have an environmental footprint and that in some cases trade-offs exist between several environmental impact categories for different feedstock (Dom enech et al, 2002;Marquevich et al, 2002;Miller et al, 2007;Righi et al, 2001). In addition, existing studies on LCA (Do Amaral, 2004;Kukfisz and Maranda, 2014;Ophus and Digernes, 1996) of emulsion chemistry point out the need to assess the environmental cost/benefits of emulsion technologies.…”
Section: Introductionmentioning
confidence: 92%
“…In a recent study from Righi et al the cellulose dissolution by BMIMCl in comparison to the dissolution in NMMO in the Lyocell process has been analyzed by a life cycle assessment (LCA). [16] It was shown, that the IL can dissolve higher amounts of cellulose with a lower time and energy consumption and that there is a small reduction of the hazardous compound emission. However, the major environmental impact is a result of the solvents syntheses.…”
Section: Processing Of Dissolved Cellulose Without Derivatizationmentioning
confidence: 98%
“…lactone has been reported using H 3 PO 4 as catalyst. [16,72] By ring opening polymerization this intermediate can be transformed into an aliphatic polyester. It is considered a valuable polymer made from renewables that is degradable by light or under acidic/basic conditions.…”
Section: -Hydroxymethylfurfural and Levulinic Acidmentioning
confidence: 99%
“…Righi et al [14] compared the expected environmental impacts of two cellulose dissolution methods, if applied at industrial production level: the well-established environmentally friendly non-viscose processes with N-methyl-morpholine-N-oxide (NMMO/H 2 O) and an alternative process with 1-butyl-3-methylimidazolium chloride (BmimCl). This case represents a situation in which the former process is already implemented at an industrial scale but no LCA dataset is available and the latter is only tested at lab scale.…”
Section: Ionic-liquid Case Studymentioning
confidence: 99%
“…Process engineering practice has developed a few tools and rules-of-thumb that are typically used to start the process design activities and that can be fruitfully exploited also in the case [11][12][13]. While it is recognized that the actual scale-up process may lead to significant improvements in the performances of a plant, this simplified approach is considered adequate for the purpose of explorative LCA studies [14,15].…”
Section: Introductionmentioning
confidence: 99%